2017
DOI: 10.3389/fmicb.2016.02160
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-coding Regulatory RNA in the Virulence of Human Pathogenic Vibrios

Abstract: In recent decades, the identification of small non-coding RNAs in bacteria has revealed an important regulatory mechanism of gene expression involved in the response to environmental signals and to the control of virulence. In the family Vibrionaceae, which includes several human and animal pathogens, small non-coding RNAs (sRNAs) are closely related to important processes including metabolism, quorum sensing, virulence, and fitness. Studies conducted in silico and experiments using microarrays and high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 114 publications
(227 reference statements)
1
16
0
Order By: Relevance
“…Additionally, several regulatory proteins involved in quorum sensing and biofilm formation, including Hfq, LuxS, and SmcR (Kim et al, 2013;Wen et al, 2016), were found to be acetylated. The role of these proteins in the regulation of virulence genes in genus Vibrio has also been widely reported (Waters et al, 2010;Pérez-Reytor et al, 2016), and our finding further shows the potential association between protein acetylation and the virulence of V. vulnificus.…”
Section: Functional Annotation and Enrichment Of Acetylated Proteins supporting
confidence: 83%
“…Additionally, several regulatory proteins involved in quorum sensing and biofilm formation, including Hfq, LuxS, and SmcR (Kim et al, 2013;Wen et al, 2016), were found to be acetylated. The role of these proteins in the regulation of virulence genes in genus Vibrio has also been widely reported (Waters et al, 2010;Pérez-Reytor et al, 2016), and our finding further shows the potential association between protein acetylation and the virulence of V. vulnificus.…”
Section: Functional Annotation and Enrichment Of Acetylated Proteins supporting
confidence: 83%
“…The autoinducer-receptor systems in V. parahaemolyticus are likely similar to those in V. harveyi, based on phylogenetic analyses and signaling assays (10,14,16,42), whereas only the LuxPQ system that detects AI-2 has been identified in V. vulnificus (40). The number of Qrrs in different Vibrio species varies from one to five among vibrios, and they act either additively or redundantly (15,45,(52)(53)(54)(55)(56). Further, the Qrr regulon in V. harveyi (ϳ20 genes) does not appear to include the type VI secretion genes, which are regulated by the Qrrs in V. cholerae (50,57).…”
mentioning
confidence: 99%
“…Small RNAs have been widely studied especially in the context of virulence regulation in pathogenic bacteria 31 , 37 , 38 , 55 . In Vibrionacea, small RNAs has been intensively studied in V. cholerae 56 . However, in other species, the role of small RNAs awaits further elucidation.…”
Section: Discussionmentioning
confidence: 99%